A clutter reduction algorithm in non-coherent LFM CW radars - Hovhannes R. Avagyan (Изд-во НАН РА)
The algorithm of clutter reduction in LFM CW radars is presented. Similarities in sequential measurements are formalized via the introduced identification function. The ensemble averaging allows significantly to simplify the moving target identification.
Keywords: Mathematics; Algorithm